Pengaruh Kemiskinan, Gini Ratio, dan Angka Partisipasi Sekolah terhadap Indeks Pembangunan Manusia di Indonesia Tahun 2011-2020 - Hidayat, Fachrudin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to analyze the influence of poverty, Gini ratio, and school enrollment rates on the Human Development Index (HDI) at the provincial level in Indonesia. This research uses quantitative methods with a panel data regression analysis approach. The research population includes all Indonesian HDI data, while the research sample consists of annual data on the variables Poverty, Gini ratio, and School Enrollment Rate (APS) in 34 provinces from 2011 to 2020. Data was collected through official statistical documentation and analyzed using a fixed effects model (fixed effect model) selected based on the Chow test and Hausman test. The research results show that poverty and the Gini ratio negatively influence HDI by -.0421 and -15.37 respectively, while APS has a positive influence of 0.269. Simultaneously, the variables Poverty, Gini Ratio, and APS have a significant effect on HDI in Indonesia worth 268,901. It appears that poverty, income inequality, and school enrollment rates significantly influence human development in Indonesia, indicating that efforts to increase HDI require attention to reducing poverty, reducing inequality, and increasing access to education